Resection of a pulmonary nodule in a transplanted lung under extracorporeal membrane oxygenation - Parrilla, Gustavo A.; Dosso, Nicolás A.; Absi, Daniel O.; Defranchi, Sebastián; Osses, Juan M.; Gonzalez, José L.; Bertolotti, Alejandro M. (Revista Argentina de Cirugía, 2021)
The use of perioperative support with extracorporeal membrane oxygenation (ECMO) systems is a novel concept in general thoracic surgery We report the case of a male patient with a history of right lung transplant due to idiopathic pulmo- nary fibrosis (IPF) who required resection of a right pulmonary nodule under veno-venous (VV) ECMO support. The use of VV-ECMO is a feasible option in selected cases when complications are expected to occur with one lung ventilation